2010
DOI: 10.1002/ejic.201000155
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of New Ligand‐Deficient Thiocyanato Compounds with Cooperative Magnetic Phenomena by Thermal Decomposition of Their Ligand‐Rich Precursors

Abstract: The reaction of nickel thiocyanate with bipy (4,4′‐bipyridine) in water at room temperature leads to the formation of the ligand‐rich 1:2 (1:2 ratio between metal salt and organic ligand) hydrate [{Ni(NCS)2(bipy)(H2O)2}·(bipy)]n (1‐Ni), which is isotypic to its analogues 1‐Mn and 1‐Co reported recently. In their crystal structure, the metal cations are coordinated by two terminal N‐bonded thiocyanato anions, two water molecules, and two bridging bipy ligands in an octahedral coordination mode. These building b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…In this case also hydrates can be obtained and there are also different solvates reported in literature. [109,111,[151][152][153] On heating the hydrates looses the water molecules in the first step, which on further heating transforms into ligand-deficient compounds of composition [M(NCS) 2 (4,4Ј-bipyridine)] n (M = Mn, Co, Ni, Fe) in the second step ( Figure 13). Magnetic investigation revealed that in all hydrates and all ligand-deficient compounds only paramagnetic behavior without any anomaly is found, whereas in the ligand-deficient intermediates with Mn, Fe, and Ni antiferromagnetic ordering is observed.…”
Section: D Coordination Polymersmentioning
confidence: 99%
“…In this case also hydrates can be obtained and there are also different solvates reported in literature. [109,111,[151][152][153] On heating the hydrates looses the water molecules in the first step, which on further heating transforms into ligand-deficient compounds of composition [M(NCS) 2 (4,4Ј-bipyridine)] n (M = Mn, Co, Ni, Fe) in the second step ( Figure 13). Magnetic investigation revealed that in all hydrates and all ligand-deficient compounds only paramagnetic behavior without any anomaly is found, whereas in the ligand-deficient intermediates with Mn, Fe, and Ni antiferromagnetic ordering is observed.…”
Section: D Coordination Polymersmentioning
confidence: 99%
“…A rich variety of coordination polymers with interesting magnetic properties, such as cooperative magnetic phenomena, have been obtained by combining paramagnetic transition metal cations and small magnetic active linker ligands. [10][11][12][13][14][15][16][17] Recently, our group have reported about a series of ligandrich 1:2 (1:2 = ratio between metal and co-ligand) thiocyanato coordination polymers [M(NCS) 2 L 2 ] n with M = Mn, Fe, Co, Ni and L = 4,4'-bipyridine, [18,19] pyrazine, [20,21] pyrimidine, [22,23] and pyridazine, [24,25] in which the small-sized thiocyanato anions are terminally N-bonded and therefore not involved into magnetic exchange interactions. We demonstrated that on heating such compounds transform into new ligand-deficient 1:1 intermediates [M(NCS) 2 L] n , in which the thiocyanato anions become μ-1,3 bridging.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, compounds with condensed networks, in which paramagnetic metal atoms are linked by small-sized anionic ligands are of special interest because of their diverse magnetic properties. Therefore, a large number of different compounds based on e. g. azides, oxalates or thiocyanates were investigated [8][9][10][11][12][13][14][15][16][17][18][19]. However, for these anions different coordination modes are known in which they are either only terminally bonded or act as bridging ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In these reactions, suitable precursor compounds based on transition metals, terminal bonded thiocyanato anions and additional coligands are heated, which compulsorily leads to the formation of liganddeficient intermediates, in which the metal atoms are then connected by the anionic ligands [14][15][16][17][18][19]. This reaction is accompanied with a dramatic change in the magnetic properties such that frequently cooperative magnetic exchange interactions are found in the ligand-deficient compounds.…”
Section: Introductionmentioning
confidence: 99%